Evolving Our Understanding and Practice in Addressing Social Conflict and Stakeholder Engagement Around Conservation Translocations - Glikman, Jenny Anne; Frank, Beatrice; Bogardus, Michelle; Meysohn, Samantha; Sandström, Camilla; Zimmermann, Alexandra; Madden, Francine (Frontiers in Conservation Science, 2022)
The conservation field has evolved to include an understanding of human values and attitudes toward wildlife; however, there is still too little emphasis on, and prioritization of, building understanding of the complex and context-specific social conflicts among people and groups involved with or impacted by conservation actions, including translocation. Both foci add value, but the latter is critical for building receptivity for conservation efforts and more thoughtfully designing appropriate context-specific processes for stakeholder engagement and shared decision-making. A deeper analysis of the social conflict dynamics involving the human relationships among individuals and groups engaged in a conservation conflict is needed as a first step in paving the way for the long-term success of conservation projects. Using a “Levels of Conflict” model offers a starting place for the analysis of social conflict often underpinning conservation translocation efforts. Further, we recommend employing a Conservation Conflict Transformation approach when considering conservation translocations to ensure that stakeholder engagement processes sufficiently engage the system, reconcile deep-rooted conflict among those involved and offer the best chance for shared progress and conservation success.